Vulnerability of long-range inputome of basal forebrain in normal aging mice - Sun, Tingting; Chen, Jiale; Liu, Bimin; Li, Anan; Gong, Hui; Li, Xiangning (Frontiers in Aging Neuroscience, 2025)
IntroductionAs the human undergoes the process of aging, it becomes evident that the elderly population exhibits age-related cognitive decline. The basal forebrain (BF) has been shown to have complex connections with the hippocampus (Hip) and medial prefrontal cortex (mPFC) through circuits, and is involved in cognitive functions. However, which circuit is most vulnerable during normal aging remains unclear.MethodsUtilizing a combination of viral tracing and fluorescence Micro-Optical sectioning tomography (fMOST), we performed quantitative analyses on the whole-brain inputs of the BF, Hip, and mPFC during normal aging.Results and discussionThe long-range inputome revealed that the nucleus of the diagonal band (NDB) of BF was vulnerability to damage, especially the connection strength of the vCA3-NDB circuit is significantly reduced, which may be related to decision making. A comparison of the 3D continuous data of BF subregions revealed that aging resulted in a weakened connection strength between each region and the olfactory areas (OLF), which obeyed a topological relationship, which might be related to the learning and memory. These results provide an anatomical foundation for understanding the selective vulnerability of BF circuit during normal aging and offer a novel perspective for future research into the treatment of age-related cognitive decline.